Quality and matabolic implications of including anchovy oil or a blend of herring oil, n-3 PUFA concentrate and palm stearin in Atlantic salmon (Salmo salar L.) diets - Menoyo, D.=700 1 Lopez Bote, C.J.; Bautista, J.M.; Obach, A.
(Es, En)
ilus., 36 ref.
Keywords: SALMO SALAR; ALIMENTACION DE LOS ANIMALES; CRECIMIENTO; DIGESTIBILIDAD; LIPOLISIS; TEXTURA; ESPAÑA; SALMON; FUENTES DE GRASA